COMPARATIVE CLINICAL EFFICIENCY ASSESSMENT OF VARIOUS LOCAL ANESTHESIA METHODS IN CURING DENTAL CARIES AND PULPITIS - Muntyan, O.V.; Muntyan, V.L.; Шинкарук – Диковицька М.М.; Beliayev, E.V.; Goray, M.A. (World of Medicine and Biology, 2019)
The clinical efficacy comparison of various local anesthesia methods was carried out in 109 patients with acute deep caries of teeth, 18 - with pulmonary hyperemia and acute traumatic pulpitis, and 25 – with acute and chronic pulpitis forms requiring local anesthesia for dental treatment. The total of 30 healthy individuals with a lack of carious lesions and pulpitis of similar teeth groups and the identical age group served as controls. For the efficient management of local anesthesia during the outpatient treatment of patients with acute deep caries of teeth, pulmonary hyperemia and acute traumatic pulpitis, the biological method for maintaining the viability of the pulp and its functions has proven the superiority of the intraosseous anesthetic method. In our opinion, anesthesia of dental manipulations in patients with acute and chronic pulpitis forms by extirpation method should be carried out by the infiltration, conduction and intraosseous methods of amide anesthetics administering with vasoconstrictor concentration of 1: 100000, which prevent pulp bleeding during treatment.
Keywords: teeth caries; pulpitis; local anesthesia